2016
DOI: 10.1111/psyp.12688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous and intermittent exercise on executive function in children aged 8–10 years

Abstract: Understanding the effects of acute exercise on executive function in prepubescent children may be important for the enhancement of school performance. This study assessed the effect of an acute bout of continuous (CONT) or intermittent (INT), moderate intensity treadmill exercise on executive function in young children. Twenty healthy children (age: 8.8 ±0.8y; height: 140 ±9cm; body mass: 36 ±11kg; boys: n= 9) performed a graded-exercise test to determine maximal oxygen uptake, and two, 15 minute submaximal bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
109
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 46 publications
0
109
1
4
Order By: Relevance
“…Additionally, the lack of change in estimated executive function over time may reflect the lack of sensitivity in the Stroop task with this population. We elected to use the Stroop task because it is relatively short, which would minimize mental stimulation during sitting, and it is a classic measure of prefrontal cortex function (MacLeod, ) that has been widely used to assess the effects of acute exercise on cognition (Faulkner et al, , ; Lambrick et al, ). Nonetheless, the young healthy participants in the current study may not have found the Stroop tasks sufficiently challenging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, the lack of change in estimated executive function over time may reflect the lack of sensitivity in the Stroop task with this population. We elected to use the Stroop task because it is relatively short, which would minimize mental stimulation during sitting, and it is a classic measure of prefrontal cortex function (MacLeod, ) that has been widely used to assess the effects of acute exercise on cognition (Faulkner et al, , ; Lambrick et al, ). Nonetheless, the young healthy participants in the current study may not have found the Stroop tasks sufficiently challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Table height was adjusted to place feet flat on the ground with a thigh to calf angle at approximately 90 degrees, which was standardized between trials. To avoid a learned effect, participants practiced the Stroop word and Stroop color tasks until completion time plateaued, as previously reported (Faulkner et al, , ; Lambrick, Stoner, Grigg, & Faulkner, ). Participants also practiced several sets of 10 calf raises at a rate of 0.33 Hz (20 per min), set to a metronome (Pro Metronome, EUMLab, Xanin Tech).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in support of the findings of Chang and colleagues (2012), whose meta‐analysis found that the greatest positive effect on cognition occurs 11–20 min after exercise cessation. More recent research has shown that improvements in cognition can be maintained for a period of at least 30 min postexercise (Lambrick, Stoner, Grigg, & Faulkner, ; Peiffer, Darby, Fullenkamp, & Morgan, ; Tsukamoto et al, ). These previous findings, together with the current findings, may have practical implications for the rehabilitation environment.…”
Section: Discussionmentioning
confidence: 99%